PERKAWINAN DI BAWAH UMUR DAN TANTANGAN DALAM MENCAPAI SUSTAINABLE DEVELOPMENT GOALS - Tan, Winsherly (Universitas Muhammadiyah Sorong, 2021)
The SDGs have a goal of empowering women and the practice of underage marriage. However, this is still happen in Indonesia. The purpose of this study is first, analyze the protection to children who are involved in underage marriages. Second, analyze the role of Indonesia in realizing the fifth goal of the SDGs. The method used in this research is normative juridical. The primary legal materials used are Law Number 16 of 2019, Law Number 35 of 2014, Law Number 25 of 2004. The theories used in this study are Theory of Legal Effectiveness by Soerjono Soekanto and Theory of Welfare by Bagir Manan. Based on the research results, the protection has not been effective because of the weak factor of substance, infrastructure, society and existing legal culture. However, the Indonesian government has a strategy in achieving the five SDGs but it has not been effective in releasing.